2015
DOI: 10.1007/s12288-015-0501-x
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of Bone Metastasis Cancer After Using Adefovir Dipivoxi in a Hepatitis B Patient with Fanconi Syndrome

Abstract: Adefovir dipivoxil is commonly used for treatment of chronic hepatitis B patients. We present a case of acquired Fanconi syndrome and hypophosphatemic osteomalacia in a patient with chronic hepatitis B who had been treated with ADV for 8 years. A 41-year-old man complained of severe bilateral hypochondrium pain and lower limb weakness, and he had the diagnosis of bone metastasis cancer or multiple myeloma. Laboratory results and radiologic findings suggested Fanconi syndrome with osteomalacia after hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, awareness of this condition seems unsatisfactory in daily clinical practice, since some patients with ADV-induced Fanconi syndrome have been undiagnosed or even misdiagnosed. Li et al (20) reported a 41-year-old man with an 8-year history of low-dose ADV therapy for HBV. He had suffered from chest wall pain and lower limb weakness over a six-month period.…”
Section: Discussionmentioning
confidence: 99%
“…However, awareness of this condition seems unsatisfactory in daily clinical practice, since some patients with ADV-induced Fanconi syndrome have been undiagnosed or even misdiagnosed. Li et al (20) reported a 41-year-old man with an 8-year history of low-dose ADV therapy for HBV. He had suffered from chest wall pain and lower limb weakness over a six-month period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early detection of abnormalities in chemical examinations and early diagnosis are particularly important for timely alleviation of patients' pain. Since Fanconi syndrome is rare, numerous physicians are unfamiliar with its symptoms and signs, thus leading to delayed diagnosis and treatment (9). Therefore, improved knowledge of Fanconi syndrome is important, particularly for hepatologists.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other nucleoside analogs, adefovir dipivoxil is characterized by low cost, low drug resistance and absence of cross-resistance, and has been applied widely in developing countries (4,5). However, renal toxicity is the most common adverse reaction associated with adefovir dipivoxil, and it has been reported to cause Fanconi syndrome (6)(7)(8), which is often misdiagnosed due to a dearth of knowledge among the majority of clinicians (9). In addition, some common manifestations of Fanconi syndrome, including systemic bone pain, osteoporosis and spontaneous fracture, are easily misdiagnosed as osteoarthrosis, osteoporosis and bone tumors in the early stages (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of 32 patients with ADV-induced FS, including eight patients in our institution and 24 published cases, are summarized in Table 4 . 5 , 18 , 22 , 23 , 36 43 …”
Section: Reviewmentioning
confidence: 99%